Effect of Li addition on the precipitation behavior of AA6061 alloy - Hyeon-Woo Son; Sung-Ho Kang; Kwangjun Euh; Yun-Soo Lee; Kyoungdoc Kim (Journal of Materials Research and Technology, 2024)
This study investigates the effect of minor Li addition on the solute clustering and thermal stability of precipitates in artificially aged Al–Mg–Si–Cu (AA6061) alloys. Li addition hinders the initial changes in hardness and electrical conductivity by delaying solute clustering during early aging. The delay in cluster formation is attributed to the disturbance of Mg enrichment by the formation of Si–Li clusters, unlike the Sn element with vacancy-trapping effect. Additionally, Li addition is found to coarsen the precipitates during over aging, thereby reducing the thermal stability of the Al–Mg–Si–Cu alloy. Gibbsian interfacial excess calculations of the Li solute indicate that the low coarsening resistance of the Li-containing precipitate is mainly caused by the small amount of equilibrium Li segregation at the internal interface between the matrix and over-aged precipitate. A decrease in the number of nucleation sites, originating from the suppression of cluster formation in the early-aging stage, is also suggested as a reason for the coarse precipitate structure. Finally, despite the high solubility of Li into precipitates, Li addition does not disorder or change the crystal structure of the precipitates. It simply increases the volume of the precipitate by an amount equivalent to or greater than the added Li, without increasing the thermal stability.